2016
DOI: 10.1108/s1479-353920150000019007
|View full text |Cite
|
Sign up to set email alerts
|

The Hopes Carry Them On: Early Educational Expectations and Later Educational Outcomes in Rural Gansu, China

Abstract: It is commonly held in the education literature that parents' and children's educational expectations are important factors in predicting children's educational achievement and attainment. However, very little is known about the significance of parents' and children's early expectations in developing country settings. This study employs a case study of children in 100 rural villages in a poor province in Northwest China to explore the impact of parents' and children's early expectations on children's later sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 60 publications
2
4
0
Order By: Relevance
“…Family SES (i.e., family economic status and parents' education levels) was not associated with discrepancies, which conflicts with previous research [33] which indicates that economically disadvantaged adolescents are more likely to have educational aspirations that exceed their expectations as they perceive more barriers. However, our results are consistent with previous research [26], which demonstrated that family SES was not related to rural students' educational outcomes and choices. In addition, the measure of family SES in the present study used a combination of indicators, which is commonly used in research from the US and the UK.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Family SES (i.e., family economic status and parents' education levels) was not associated with discrepancies, which conflicts with previous research [33] which indicates that economically disadvantaged adolescents are more likely to have educational aspirations that exceed their expectations as they perceive more barriers. However, our results are consistent with previous research [26], which demonstrated that family SES was not related to rural students' educational outcomes and choices. In addition, the measure of family SES in the present study used a combination of indicators, which is commonly used in research from the US and the UK.…”
Section: Discussionsupporting
confidence: 92%
“…In the Chinese context, many parents in rural areas recognise education as the means for upward mobility [25] and subsequently set high educational aspirations for their children, which may in turn influence children's aspirations. However, educational resources are more limited in rural areas [26], and lack of parental support (especially for LBC) makes it more difficult to achieve good educational outcomes [27].…”
Section: Introductionmentioning
confidence: 99%
“…Zhao and colleagues [33] examined correlates of problem behaviors among children affected by HIV and found that low educational aspirations had direct negative effects on school adjustment. Children's early expectations were strong predictors of children's chances of staying in school, completing compulsory education and completing secondary education as well [34]. Zhang [34] found that future orientation had positive influences on junior secondary school students' learning attitude, academic help-seeking behavior and academic achievement.…”
Section: Academic Outcomesmentioning
confidence: 99%
“…Children's early expectations were strong predictors of children's chances of staying in school, completing compulsory education and completing secondary education as well [34]. Zhang [34] found that future orientation had positive influences on junior secondary school students' learning attitude, academic help-seeking behavior and academic achievement. Chen [35] also found that university students who were more future-oriented were more engaged in their studies.…”
Section: Academic Outcomesmentioning
confidence: 99%
“…For Chinese rural children, getting into higher education is considered as the only opportunity to change their fate (commonly known "jump into the dragon gate" Tiao long men 跳龙门) by permanently leaving the poor countryside (Annunziata et al 2006). In the Chinese context, Zhang's (2012) longitudinal study found that parents' and children's shared high expectations of educational attainment and college completion predict success for poor rural students.…”
Section: Chinese Culture/context and The Present Studymentioning
confidence: 99%